Integration of Venezuelan migrants in the tourism labor market in Peru: a case study of regulated travel agencies in Lima - Duthurburu, Marissa; Rivas Medina, Cecilia; Cherro Osorio, Sandra (Frontiers in Sustainable Tourism, 2023)
Between 2015 to 2019, Peru became the second biggest host community for displaced Venezuelans, and 4 out 5 chose the capital, Lima, as their destination. While the majority of migrants found jobs in the tourism and hospitality industries, only a minority were employed in the regulated sector of tourism and hospitality, with the majority finding employment in what is considered the unregulated sector. This study presents an analysis on the role of regulated travel agencies in the process of the social and economic integration of Venezuelan migrants in the host country. A qualitative method was employed with in-depth interviews to migrants, migration experts and formal employers in the tourism sector. A total of 12 interviews took place during June to November 2020. It should be noted that the study took place during lockdowns so the sample size is relatively small due to the closure of travel agencies and the challenges on identifying participants. Findings indicate that regulated travel agencies represent a good medium for the integration of Venezuelan migrants as they create professional opportunities for skilled professionals and promote safe multicultural spaces that foster social integration. However, challenges were also recognised as migrants tend to be overqualified for the roles they performed and are also faced with gender inequality and other forms of discrimination by local society. This study proposed that given their professional qualifications Venezuelan migrants have the potential to contribute in the recovery of the tourism sector particularly after the pandemic. However, current unwieldy migration policies may deter them to reach job opportunities in the sector.